PENGEMBANGAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI PEMBUATAN JAJE SUCI DI PRATAMA WIDYA PASRAMAN GURUKULA BANGLI - Yanti, Ni Luh Gede Mega; Suryawan, I Gde; Deniati, Gusti Ayu Sri (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2023)
Growth and development experience a rapid increase at an early age, namely the age of birth to six years, therefore children need physical activity stimulation according to their respective abilities, both physical activities related to gross motor movements and fine motor movements. Fine motor skills are a child's ability to carry out activities that involve good eye-hand coordination. There are several activities that can stimulate children's motor development such as squeezing paper, tearing, scribbling, coloring, cutting, playing plasticine, and making collages. Pratama Widya Pasraman Gurukula Bangli which is a Hindu-based Kindergarten implements activities related to the culture and traditions of the Hindu community in Bali that can be used to stimulate children's fine motor development, the activity in question is making sacred jaje. Jaje suci is a ritual equipment made by the community as a means of ritual to complement ceremonies in Bali. In making this holy jaje, children will be given media in the form of flour dough. This type of research is a descriptive qualitative research with a phenomenological approach. The data collection techniques used are observation, interviews, literature studies and documentation, with data analysis techniques using the Miles & Huberman model which consists of three lines, namely data reduction, presentation of data analysis results and drawing conclusions. . The results of this study indicate that the application of making holy jaje can stimulate children's fine motor skills because the manufacturing process involves good hand and eye movement skills, besides making this holy jaje can also stimulate children's cognitive abilities.